WORK POSTURE IMPROVEMENT AT PLASTIC PRINTING PROCESS IN PLASTIC MANUFACTURING INDUSTRY - Mohamed, M.S.S.; Halim, I.; Azani, A.H.; Saptari, A. (Journal of Advanced Manufacturing Technology (JAMT), 2019)
Plastic printing workstations in the plastic manufacturing industry are still semi-automated exposing operators to various ergonomics risk factors. This study aims to redesign the existing plastic printing workstation for improving work posture to prevent the occurrence of work-related musculoskeletal disorders (WMSD). The ergonomics risk factors faced by ten plastic printing workstation operators were assessed using workplace observation, questionnaire survey and Rapid Upper Limb Assessment (RULA). The results showed the operators were subjected to frequent bending posture which may cause WMSD on the back, shoulder, and legs. A new workstation design concept was constructed and finalized using the House of Quality (HOQ). This study concluded that the new design of the workstation has improved the RULA score from 7 to 3. Further investigation is recommended on the productivity and product quality analysis, and muscle activity of the operators in the future study.